RESPONS HAMA Spodoptera litura F. TERHADAP PESTISIDA BOTANIS Cymbopogon nardus L Rendl., Pangium edule Reinw., dan Syzigium aromaticum L. PADA TANAMAN Brassica olearacea L. - Kojongian, Indra Y.; Rumokoy, Laurentius J. M.; Pinaria, Betsy A. N. (Sam Ratulangi University, 2022)
This study aims to studying the effect of extracts of citronella, pangi leaves, and clove leaves on the mortality of S. litura larvae, the number of S. litura pupae formed and the inhibition of feeding activity of S. litura larvae on cabbage plants. This research was conducted at the Laboratory of the Protection and Quality Testing of Food Crops and Horticulture of North Sulawesi Province and the Laboratory of the Agriculture and Fisheries Service of Tomohon City from November 2020 to July 2021. The research method used a completely randomized design consisting of 3 treatments and 5 replications. The results showed that citronella extract, pangi leaf extract and clove leaf extract could control the mortality of S. litura larvae, the number of pupae of S. litura larvae formed and inhibit the feeding activity of S. litura larvae.